Pachylis nervosus Dallas, 1852 and Pachylis pharaonis (Herbst, 1784) (Hemiptera: Coreidae) associated with Pithecellobium dulce (Roxb.) Benth. (Fabales: Fabaceae) in Arraiján, Panamá Oeste, Panama. (Aporte Santiaguino, 2023)
The aim of the study was to identify the bug species associated with Pithecellobium dulce (Fabales: Fabaceae) in Arraiján, Panamá Oeste, Panama; describing the different development stages of the insect. Periodic observations were made (December 2022 – April 2023), reviewing ornamental plants, surrounding vegetation and photographic records. Bug specimens were collected for identification in the laboratory, consulting specialized literature. According to the results, two species were identified: Pachylis nervosus Dallas, 1852 and Pachylis pharaonis (Herbst, 1784) (Hemiptera: Coreidae), the first is present from Mexico to Colombia and Ecuador; the second is found in Costa Rica, Panama and several South American countries. Pachylis eggs are black and oval, with a flattened operculum and laid in groups of up to 80 eggs; the first instar nymphs have a black head, antennae, thorax and legs, with a reddish abdomen; the nymphs of more advanced stages have black, reddish, yellow and blue pigmentation, similar to that observed in other Coreidae; teneral individuals are ocher in color. The differentiation between species was achieved with adults, only. The insects were also observed on other ornamental species. In conclusion, P. nervosus and P. pharaonis are the bug species associated with P. dulce in Arraiján, Panama.
Keywords: Associated vegetation; Bug; Legume; ornamental plants; Panamá Oeste